Geografia e livro didático: representação dos povos indígenas - Guites, Airton Rosa Lucion (2019)
The Brazil is a plural nation, formed through the mixing of differents ethnicities, among which there are indigenous people. Geography, being a science dedicated to studying the relationship between society and nature, must analyze the indigenous question from the perspective of territoriality, space organization and social participation as political agents. The indigenous people went through different stages in the historiography of the country, but a characteristic always present was the acculturation process imposed by the European colonizer that stayed in the implied sense even after the Independence. For Geography understands the articulations of indigenous people in the Brazilian territory of the 21st century, it is imperative to refer back to the past, understanding how the indigenous participated in the formation of Brazil at the same time as they were "erased" by the ethnic transfiguration. Under the bias of education, the Geography as a school discipline has the duty to consider the issue of indigenous people, although this does not always happen in a satisfactory way. Through teaching materials, such as textbooks, the geography is embedded in the educational field and offer students the development of the ability to observe, interpret and reflect reality. Although there are many methodological critiques about textbooks, they still are the materials of increased access and dissemination in Brazilian schools. Thus, we have the theme of this research, which is the representation of indigenous people in Geography textbooks. The problem that will guide the research will be: the textbooks of Geography represent the indigenous as social and political agent of space? In order to answer this question, was analyzed and investigated, by specific criteria, the way indigenous people are approached by Geography in books of this segment for several decades. Therefore, teachers from Santa Maria/RS were interviewed to understand their view about this subject. As a result, the textbooks were divided into three periods, which presented a methodological evolution about the indigenous approach, but that still has many aspects to improve. Regarding teachers, it was noticed that there was no focus on the theme throughout their academic education, which impairs their teaching performance.